Heavy Metal Pollution of Soil and Vegetable Grown Near Roadside at Gazipur (Bangladesh Journal of Agricultural Research, 2012)
Levels of lead, cadmium, and nickel in roadside soils and vegetables along a  major highway in Gazipur, Bangladesh were investigated. Soil samples were  collected at distances of 0, 50, 100, and 1000 m (meter) from the road. The  concentrations of lead (Pb) and nickel (Ni) in soil and vegetables (bottle gourd  and pumpkin) decreased with distance from the road, indicating their relation to  traffic and automotive emissions. The concentration of cadmium (Cd) was found  to be independent of distance from road. There were significant differences in  the concentrations of lead, cadmium, and nickel for different plant species and  soils at various distances. The heavy metals contents both in the soils and  vegetables for every distance from the road was found in the order  nickel>lead>cadmium. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11170 Bangladesh J. Agril. Res. 37(1): 9-17, March 2012